TÍNH TOÁN UỐN VÀ DAO ĐỘNG TẤM COMPOSITE GẤP NẾP BẰNG PHƯƠNG PHÁP PHẦN TỬ HỮU HẠN - Thịnh, Trần Ích; Tú, Trần Minh; Bình, Bùi Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARY BENDING AND VIBRATION ANALYSES OF FOLDED COMPOSITE PLATE BY FEM This paper presented an analysis of static and free vibration of laminated composite folded plate using finite element method, based on the first order shear deformation theory. In this analysis, a sixth drilling degree of freedom (DOF) () corresponding to the rotation about the z axis is added to the existing 5 DOF system (,,,,). The effects of fibbers orientation, crank angles (folding angle) on the deflections, on natural frequencies of folded plate structures were determined. The present results have been compared with published one (where available). It is shown that concordance between the two sets of results. Keyword. folded composite plate, finite element method, folded plate element, Mindlin theory, static and dynamic analysis, mode sharp